2017
DOI: 10.1002/2211-5463.12340
|View full text |Cite
|
Sign up to set email alerts
|

Effects of O‐methylated (−)‐epigallocatechin gallate (EGCG) on LPS‐induced osteoclastogenesis, bone resorption, and alveolar bone loss in mice

Abstract: (−)‐Epigallocatechin‐3‐ O ‐gallate ( EGCG ), present in green tea, exhibits antioxidant and antiallergy effects. EGCG 3″Me, a 3‐ O ‐methylated derivative of EGCG , has been reported to show similar biological functions; the inhibitory activity of EGCG 3″Me in a mouse allergy model was more potent than that of EGCG , probably due to the efficiency of ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Furthermore, in human PBMCs, these aminothiazoles, targeting mPGES‐1, reduced the LPS‐induced PGE 2 production as well as inhibited the RANKL‐stimulated osteoclastogenesis and bone resorption in the current study. Another study by Tominari et al showed that osteoclast differentiation from RANKL‐stimulated mouse bone marrow macrophages is suppressed by compounds inhibiting PGE 2 synthesis by targeting both COX‐2 and mPGES‐1. Both RANKL‐RANK and LPS‐TLR4 signalling pathways are mediated via transcription factor NF‐κB.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in human PBMCs, these aminothiazoles, targeting mPGES‐1, reduced the LPS‐induced PGE 2 production as well as inhibited the RANKL‐stimulated osteoclastogenesis and bone resorption in the current study. Another study by Tominari et al showed that osteoclast differentiation from RANKL‐stimulated mouse bone marrow macrophages is suppressed by compounds inhibiting PGE 2 synthesis by targeting both COX‐2 and mPGES‐1. Both RANKL‐RANK and LPS‐TLR4 signalling pathways are mediated via transcription factor NF‐κB.…”
Section: Discussionmentioning
confidence: 99%
“…Our study shows that inflammatory factors in children with ankle fractures are significantly higher than those in healthy children. It has been reported that BK stimulates bone resorption in mice [ 22 ]. A previous study has reported that SIN reduces osteoclasts activity and bone resorption both in vivo and in vitro via inhibition of inflammation and immune responses [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that ECG inhibits the biofilm formation of periodontal pathogens, such as P. gingivalis and Prevotella intermedia (11). It has been demonstrated that EGCG inhibits the resorption of alveolar bone induced by lipopolysaccharide (LPS) in mice suffering from periodontitis (12). In a preliminary clinical trial, the local application of green tea in the form of mouthwash or dentifrice was shown to produce an improved effect comparable to that of CHX on chronic periodontitis (13,14).…”
Section: Evidence Of the Inhibitory Effect Of Various Naturally Occurmentioning
confidence: 99%